#ME TOO. Issue 1 (2nd January 2021) - Downey, Hilary
ABSTRACT: Poetic reflection employed in #ME TOO takes the reader journeying across many shadows of vulnerability, drawing on intimate experiences, before rippling out to garner others flesh witnessing, tangled up in moving tales. This poetic reflection seeks to valorise consumers' life stories to claim certitude of flesh-witnessing of first-hand subjective narratives of traumatic experiences. Layers of suppressed vulnerability peeled back to reveal deeper scar tissue, afforded space to germinate, mutate, even yet, in institutional farmyards where voices quieted, deserve attention. The mores of disruption and despair, heaped high, call out in everyday timbres, now given space to breathe on the open page. This poetic reflection calls to action, reflection, subjection, those tinkering in the shadows, edgeworkers ebbing extinction, to vocalise experiences and usher in corridors of change. These poetic expressions embracing emotionality encircled in the wider nuances of #ME TOO.